2001
DOI: 10.1111/j.1749-6632.2001.tb03566.x
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Hormones Modulate Cocaine‐Induced Locomotor and Stereotypic Activity

Abstract: Interactions between ovarian hormones and cocaine may underlie gender and estrous cycle differences in cocaine‐induced behavioral and neurochemical alterations. The aim of this study was to further understand how ovarian hormones modulate cocaine‐induced behavioral alterations. Ovariectomized rats received acute or chronic saline or cocaine (15 mg/kg i.p.) administration and were further subdivided into one of four hormone‐treatment conditions: cholesterol (vehicle‐control), estrogen, progesterone, or estrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 23 publications
2
20
1
Order By: Relevance
“…Previous studies have also found that ovariectomy decreases or delays behavioral sensitization to cocaine and also decreases self-administration behavior in female rats (12). However, although previous studies have not found a significant increase in stereotypy behavior after acute or repeated cocaine administration in OVX rats (9,29), we found that acutely administered or cocaine-sensitized OVX rats had more stereotypy behaviors than control (saline-injected) rats. Curiously, exogenous progesterone, with or without estradiol, abolished these stereotypy behaviors in the OVX rats.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies have also found that ovariectomy decreases or delays behavioral sensitization to cocaine and also decreases self-administration behavior in female rats (12). However, although previous studies have not found a significant increase in stereotypy behavior after acute or repeated cocaine administration in OVX rats (9,29), we found that acutely administered or cocaine-sensitized OVX rats had more stereotypy behaviors than control (saline-injected) rats. Curiously, exogenous progesterone, with or without estradiol, abolished these stereotypy behaviors in the OVX rats.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, in addition to promoting reinstatement of cocaine-seeking behavior, cocaine may have also caused increased locomotor activity in these animals. The finding that the OVX + EB rats had greater inactive lever responding than OVX + DMSO rats is consistent with several studies that found that the locomotor activity produced by cocaine, at similar bolus doses that were used in the present study, was enhanced by estrogen treatment (eg, Sell et al, 2000Sell et al, , 2002Perrotti et al, 2001;Chin et al, 2002). Interestingly, in contrast to what was found for active lever responding, the effect of EB on inactive lever responding was also found in rats pretreated with PPT, but not those pretreated with DPN.…”
Section: Er Activation and Inactive Lever Responding During Reinstatesupporting
confidence: 93%
“…Also, the administration of PROG in estrogen-treated ovariectomized rats decreased stimulantinduced behaviors relative to ovariectomized rats treated with estrogen alone Jackson et al 2006;Larson et al 2005Quinones-Jenab et al 2000). Administering PROG alone had negligible effects on stimulant-induced behavior in ovariectomized female rats (Perrotti et al 2001;Quinones-Jenab et al 2000;Sell et al 2000;Sircar and Kim 1999). A limitation of the present study was that the estrous phase and hormone levels were not controlled for; thus, we could not examine estrogen-ALLO interactions on cocaine seeking.…”
Section: Discussionmentioning
confidence: 94%